Characterization of surface properties of carbon black and graphite - Peukert, Wolfgang; Götzinger, Martin (Annales Universitatis Mariae Curie-Sklodowska, Sectio AA Chemia, 2002)
Carbon black is used in several technical applications. Fillers in tires, black pigments in printing technology or synthetic cloth fibers are only a few examples. Because of the small particle size of carbon blacks, the surface properties have a great influence on the product property . We studied two different carbon black that show a large difference up to 20% in rolling drag when used as filler in tires. Different roughness or diverse polar groups on the surfaces are possible reasons for this. Morphology, surface structure and chemical surface composition of carbon black are not well defined. For such systems, TGA-MS and gas adsorption are powerful tools to analyze surface properties. We use adsorption equilibria in the Henry-region that reflect the interaction of molecules with the particle surfaces. From measured Henry-coefficients and known atomic surface structure, dispersive interaction parameters of the solid, e.g. a Hamaker-constant, can be determined by inversely solving the applied adsorption model. This method can be used to characterize carbon black if the interactions of different molecules with carbon atoms are calibrated on a defined surface like graphite. From known interaction potentials of various probe molecules, structural information like surface roughness of carbon black can be determined
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.charac